The Urgency of Legal Protection for Indonesian Health Workers in the Israel-Palestinian Conflict Area From the Perspective Act Number 59 of 1958 - Kelvin Nathaniel; Evelyn Winarko; Nicholas Alexander Indrawila; Christian Bima Ersananta (Dinasti Research, 2024)
The Geneva Conventions of 1949, which were later ratified in Law No. 59 of 1958, became the only legal basis for the protection of Indonesian health personnel in conflict zones. However, The Geneva Conventions of 1949 which were ratified by Indonesia did not provide a full explanation of the legal protection of Indonesian health personnel who are in conflict zones. Therefore the presence of the Additional Protocol of 1977 was created to complement the existing rules in The Geneva Conventions of 1949, one of the topics is about detailed regulations related to the protection of health personnel in conflict zones that until now have not been ratified by Indonesia Government. This research is normative legal research using a conceptual approach. The data that used in this study includes secondary data consisting of analysis of laws and regulations, books, scientific articles, journals, and previous research results.